Genetic Variation among Natural and Laboratory Colony Populations of Lutzomyia longipalpis (Lutz & Neiva, 1912)(Diptera:Psychodidae) from Colombia - Lanzaro,Gregory C (Instituto Oswaldo Cruz, Ministério da Saúde, 1998)
Genetic diversity among three field populations of Lutzomyia longipalpis in Colombia was studied using isozyme analysis. Study sites were as much as 598 km apart and included populations separated by the eastern Cordillera of the Andes. Genetic variability among populations, estimated by heterozygosity, was within values typical for insects in general (8.1%). Heterozygosity for field populations were compared with a laboratory colony from Colombia (Melgar colony) and were only slightly lower. These results suggest that establishment and long term maintenance of the Melgar colony has had little effect on the level of isozyme variability it carries. Genetic divergences between populations was evaluated using estimates of genetic distance. Genetic divergence among the three field populations was low (D=0.021), suggesting they represent local populations within a single species. Genetic distance between field populations and the Melgar colony was also low (D=0.016), suggesting that this colony population does not depart significantly from natural populations. Finally, comparisons were made between Colombian populations and colonies from Brazil and Costa Rica. Genetic distance values were high between Colombian and both Brazil and Costa Rica colony populations (D=0.199 and 0.098 respectively) providing additional support for our earlier report that populations from the three countries represent distinct species